Theory of Planned Behavior and Social Cognitive Theory on the Effect of the Community Health Center Tertiary Preventive Behavior among Patients with Type 2 Diabetes Mellitus: A Multilevel Analysis - Yudi Andriyaningtiyas; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: Type 2 diabetes mellitus (DM) accounts for 90% to 95% of all diabetes cases. Complications of type 2 diabetes increase the risk of death for sufferers. Complications and deaths from type 2 diabetes can be prevented by changes in behavior. This study aimed to determine the effect of health centers and other factors on the prevention of tertiary diabetes type 2, using the theory of planned behavior and social cognitive theory.Subjects and Method: This was an analytic observational study with cross sectional design, conducted at 25 community health centers, in Bantul Regency, Yogyakarta, Indonesia. A sample of 200 type 2 DM patients was selected by exhaustive sampling. The dependent variable was type 2 DM tertiary prevention. The independent variables at level 1 are intention, attitude, subjective norm, perceived behavior control/ self-efficacy, experience, modelling, self-regulation, and outcome expectation. Community health center was an independent variable at level 2. The data were collected by questionnaire and analyzed by a multilevel multiple linear regression.Results: Tertiary preventive behavior in type 2 DM patients increased with strong intention (b= 1.19; 95% CI= 0.62 to 1.76; p <0.001), positive attitude (b= 1.19; 95% CI= 0.58 to 1.80; p <0.001), supportive subjective norm (b= 0.79; 95% CI= 0.12 to 1.45; p= 0.019), perceived behavior control (b= 1.16; 95% CI= 0.60 to 1.72; p <0.001), abundant experience (b= 0.65; 95% CI= 0.62 to 1.25; p<0.001), strong modelling (b= 1.07; 95% CI= 0.53 to 1.67; p= 0.030), strong self-regulation (b= 0.87; 95% CI= 0.34 to 1.40; p= 0.001), and positive outcome expectation (b= 0.82; 95% CI= 0.25 to 1.38; p = 0.004). Community health center had contextual effect on the tertiary preventive behavior in type 2 DM patients with ICC= 19.18%.Conclusion: Tertiary preventive behavior in type 2 DM patients increases with strong intention, positive attitude, supportive subjective norm, perceived behavior control, abundant experience, strong modelling, strong self-regulation, and positive outcome expectation. Community health center has contextual effect on the tertiary preventive behavior in type 2 DM patients.Keywords: tertiary prevention behavior, type 2 diabetes, TBP, SCT, multilevel analysis.Correspondence: Yudi Andriyaningtiyas. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36A, Surakarta. Email: yudi.andriyaningtiyas@gmail.com. Mobile: +6281392704899Journal of Health Promotion and Behavior (2020), 05(01): 59-71https://doi.org/10.26911/thejhpb.2020.05.01.08